The influence of knowledge-intensive service industry agglomeration in the Yangtze River Delta urban agglomeration on regional economy - Xuejiao Zhao (Heliyon, 2024)
Knowledge-intensive service industry has become an important part of social economy, which not only promotes the innovation of modern service industry, but also promotes the upgrading and transformation of manufacturing industry. The agglomeration of knowledge-intensive service industry is not only the inevitable result of economic growth, but also the premise of sustained economic growth. Moreover, China's national economy is transforming from an industrialized economy to a service-oriented and knowledge-based economy, and the importance of knowledge-intensive service industry is increasing day by day. This paper constructs a theoretical framework of the influence of population agglomeration on the economic development of urban agglomerations. The article holds that population agglomeration promotes the economic development of urban agglomerations through the upgrading of industrial structure and the promotion of human capital. In the future, we need to focus on the similarities and differences between population agglomeration and economic development of urban agglomerations in central China, explore the factors of economic development of urban agglomerations, and provide reasonable suggestions for the government to formulate relevant economic policies. This paper, from an innovative research perspective, based on the perspective of population agglomeration, studies the path of its role in regional economic development, which can make up for this defect to some extent. Moreover, the research object has been innovated and the research method has been improved. On the basis of the above, the panel data of the Yangtze River Delta from 2012 to 2021 is selected as the research sample, the location entropy index is taken as the explanatory variable, the regional gross domestic product (GDP) is taken as the explanatory variable, and the rationality of economic theory and the significance of econometric test are considered. Finally, the data are analyzed and tested by regression. The empirical analysis of the Yangtze River Delta urban agglomeration proves the importance of knowledge-intensive service industry agglomeration to regional economic development. Finally, based on the contribution of knowledge-intensive service industry agglomeration to regional economy, the development of knowledge-intensive service industry and the promotion of industrial agglomeration are studied.